Team Pair Solo–Based IPAS Learning for Enhancing Collaboration and Attitudes in Grade VI Students - Hastuti, Dwi Miya; Elpisah, Elpisah; Radjab, Andi Mulyadi (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
This classroom action research investigates efforts to enhance sixth-grade students’ ability to work together in Natural and Social Sciences (IPAS) learning at UPT SDN Unjuruiya No. 45 Selayar Islands by implementing the Team Pair Solo cooperative learning model. The study was conducted to address students’ low collaboration skills and limited positive learning attitudes, which impeded the achievement of optimal learning outcomes. Through two learning cycles consisting of sequential group (team), pair, and individual (solo) activities, the research aimed to improve students’ cooperative abilities and attitudes toward IPAS learning. Data were collected through observation, field notes, and learning attitude assessments, then analyzed descriptively to determine changes in performance. The findings indicated a significant improvement in students’ cooperative skills, as reflected in the increase in the average percentage of collaboration indicators from 69% in Cycle I to 92% in Cycle II, covering aspects of participation, communication, responsibility, tolerance, and emerging leadership. Furthermore, students’ learning attitudes also improved, with mastery increasing from 45% in the initial condition to 100% in Cycle II, and an average score of 87 surpassing the minimum completeness criterion (KKTP) of 70. These results demonstrate that the Team Pair Solo model effectively fosters collaboration while strengthening students’ discipline, responsibility, and enthusiasm in learning. Thus, the model is proven to be a relevant strategy for enhancing cooperative skills and positive learning attitudes in IPAS instruction at the elementary level.